PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA CALON GURU MELALUI PEMBELAJARAN REFLEKTIF - rohana rohana (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2017)
This research aims to investigate the  enhancement of mathematical communication ability of prospective teachers’ through Reflective Learning. This research used a quasi-experimental design with nonequivalent pre-test and post-test control-group design. The subjects of this study were students of Mathematics Education Program at a private university in Palembang, consisting of 64 students. Based on instructional factors, there were two groups of samples used in this study:  experimental and control groups. The experimental group was given Reflective Learning (RL), while the control group was given Conventional Learning (CL). Based on the result of prior mathematical knowledge test, there were three categories, namely: higher, mediocre, and lower. Data collection instruments consist of prior mathematical knowledge test and mathematical communication ability test. Data analysis that was used were t-test and  two-way ANOVA. Based on data analysis, the result obtained from this study are: 1) the  enhancement of students’ mathematical communication ability who received RL are better than those of students who received CL;  2) there is no significant interaction effect between instructional factors (RL and CL) and prior mathematical knowledge (higher, mediocre, lower) toward the students’  enhancement mathematical communication ability. Keywords: Reflective Learning, mathematical communication ability.